Spectroscopic Characterization of Iron Slags from the Archaeological Sites of Brâncoveneşti, Călugăreni and Vătava Located on the Mureş County (Romania) Sector of the Roman Limes - Enikő Bitay; Irina Kacsó; Claudiu Tănăselia; Dana Toloman; Gheorghe Borodi; Szilamér-Péter Pánczél; Zsombor Kisfaludi-Bak; Erzsébet Veress (Applied Sciences, 2020)
Iron slag samples unearthed from archaeological sites lying on the Eastern limes sector of Roman Dacia (the Brâncoveneşti and Călugăreni auxiliary forts and the Vătava watchtower) were studied in order to assess the probability of local iron working (smelting and smithing) during the 2nd–3rd centuries CE. Structural-mineralogic aspects revealed by PXRD analysis and FTIR spectroscopy indicate different slag types corresponding to different iron production and processing stages allowing the supposition that refining of the bloom and processing of the refined iron took place on the sites. The FTIR absorption bands obtained in the spectral domain 2000–400 cm−1 show that mineralogically the samples are constituted mainly of silicates associated with minor quantities of aluminates and carbonates. The fayalite, haematite, and magnetite phases appearing on both the X-ray diffractograms and the FTIR spectra agree with the redox conditions of the slag formation process which result from the Fe3+/Fe2+ ratio determined using the EPR-method. The bulk macro-elemental PXRF and ICP-MS spectroscopy data support the slag typization proposed on the basis of the probable working conditions; trace-elemental bulk composition suggests that the provenance of the raw materials may be different.